2021
DOI: 10.1177/0899764021998454
|View full text |Cite
|
Sign up to set email alerts
|

Are Disasters Disastrous to Nonprofit Organizations? Investigating the Financial Implications of Hurricane Sandy for Nonprofits

Abstract: Nonprofit organizations are sensitive to external disasters due to their high reliance on external funds and volunteers. In this study, I investigate how disasters affect the financial health of nonprofits and what factors make them more vulnerable within the context of disaster. The sample in this study includes nonprofits directly and indirectly affected by Hurricane Sandy. Using a logistic regression model, I explore if the disaster contributed to the likelihood of a nonprofit experiencing financial distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Hypothesized resource pressures through internal stakeholders are evidenced for resources coming from employees and operational volunteers. Financial pressures, that seem to concur with external shocks (Chen, 2021;Grønbjerg et al, 2020;Lin & Wang, 2016;Shi et al, 2020), are confirmed in our analysis. Moreover, our results disclose various affected nonprofit resource channels.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Hypothesized resource pressures through internal stakeholders are evidenced for resources coming from employees and operational volunteers. Financial pressures, that seem to concur with external shocks (Chen, 2021;Grønbjerg et al, 2020;Lin & Wang, 2016;Shi et al, 2020), are confirmed in our analysis. Moreover, our results disclose various affected nonprofit resource channels.…”
Section: Discussionsupporting
confidence: 80%
“…The communications aimed at gathering information, sharing information and establishing or improving connections/collaborations. Initiating or increasing collaborations (Mosley et al, 2012), establishing strategic partnerships (Arik et al, 2016;Searing et al;2021) and advocacy (Mosley et al, 2012;Searing et al, 2021) are tactics often evidenced during financial shocks. Transparency to stakeholders is an essential leadership trait, sharing instrumental knowledge is a frequently used sensegiving framework (Gilstrap et al, 2016) and informing is an appropriate response technique during victim cluster crises (Coombs, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study extends beyond recent COVID-19 and disasterrelated research (Chen, 2022;Kim & Mason, 2020) by examining the communication capabilities and purposes that nonprofits apply, and also by not relying solely on economic explanations for their response strategies.…”
Section: Summary Of Resultsmentioning
confidence: 92%